Effect of regional original income and balanced funds on capital expenditures with economic growth as moderating - Puspita, Dihan Tari Woro; Komala, Lenda (Taxation and Public Finance, 2023)
This study aims to examine the effect of Regional Original Income and Balanced Funds on Capital Expenditures with Economic Growth as Moderating Variables and their Review from an Islamic Perspective. This research method uses quantitative research using secondary data obtained from the PPID of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) in the form of Regional Government Financial Reports (LKPD) regarding Budget Realization Reports in DKI Jakarta Province for Fiscal Year 2017-2021. The sampling technique in this study used a saturated sample, and the data obtained were 5. The analytical method used was multiple linear regression analysis with SPSS version 25.0 application. The results of this study indicate that Regional Original Income and Balancing Funds do not affect Capital Expenditures, Economic Growth does not moderate the influence of Regional Original Income and Balancing Funds on Capital Expenditures. and overall, from an Islamic perspective, all related variables have met Islamic law as stated in the Al-Quran and Hadith.